Long-Term Care in Europe A Juridical Approach (Springer International Publishing, 2018)
This book provides a comprehensive overview on the long-term care systems in 12 EU member states and Norway. Focusing on the legal background and its main principles, it includes a comparative analysis which highlights the principal dissimilarities between European long term care benefits, but at the same time also a variety of features in common. It also discusses the increasingly transnational dimension of long-term as a result of migrants returning to their country of origin in old age, and the still-unsolved legal problem of entitlement to long-term care benefits in another EU-member state.